The Utilization of the Instagram Platform as a Media for Arabic Language Development in the Industrial Era 4.0 - Asni Furoidah; Koriyoh Salaeh (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
The use of traditional learning media is considered less relevant in the era of the Industrial Revolution 4.0. Instagram is a social media platform based on images and videos. It allows users to upload photos and videos, edit them, add filters, and adjust the content before sharing it with followers or as short stories. Naturally, this attracts the interest of young people. Therefore, the existence of the Instagram platform is expected to rekindle students' enthusiasm for learning Arabic, especially among members of the Muntadā al-‘Arabī community. This research examines the impact of using the Instagram platform within the Muntadā al-‘Arabī community at Assunniyyah Kencong Jember. The study employs a qualitative research method, focusing on applying Instagram as a learning tool for Arabic among students in this community. Data were collected through observation, interviews, and documentation. The findings reveal that the implementation of the Instagram platform has successfully revived students' motivation to learn Arabic, primarily through Arabic learning content shared on Instagram.